2017
DOI: 10.1158/1078-0432.ccr-16-3065
|View full text |Cite
|
Sign up to set email alerts
|

Immuno-oncology Trial Endpoints: Capturing Clinically Meaningful Activity

Abstract: Immuno-oncology (I-O) has required a shift in the established paradigm of toxicity and response assessment in clinical research. The design and interpretation of cancer clinical trials has been primarily driven by conventional toxicity and efficacy patterns observed with chemotherapy and targeted agents, which are insufficient to fully inform clinical trial design and guide therapeutic decisions in I-O. Responses to immune-targeted agents follow nonlinear dose–response and dose–toxicity kinetics mandating the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
103
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 127 publications
(105 citation statements)
references
References 83 publications
2
103
0
Order By: Relevance
“…For this reason, there is a clear need to develop biomarkers that predict toxicity in this setting. Patient-Reported Outcomes (PRO) and Quality of Life (QOL) studies may yield important insights and are discussed further by Anagnostou et al in this series (74). For example, a recent analysis of patient-reported outcomes from the CheckMate-067 trial showed differences in QOL, global health, and symptom burden between patients with melanoma treated with nivolumab, ipilimumab or the combination, which allows us to consider whether patients are willing to tolerate significant toxicities if survival is higher (75).…”
Section: Biomarker Selection Must Incorporate Patient Perspective Andmentioning
confidence: 91%
“…For this reason, there is a clear need to develop biomarkers that predict toxicity in this setting. Patient-Reported Outcomes (PRO) and Quality of Life (QOL) studies may yield important insights and are discussed further by Anagnostou et al in this series (74). For example, a recent analysis of patient-reported outcomes from the CheckMate-067 trial showed differences in QOL, global health, and symptom burden between patients with melanoma treated with nivolumab, ipilimumab or the combination, which allows us to consider whether patients are willing to tolerate significant toxicities if survival is higher (75).…”
Section: Biomarker Selection Must Incorporate Patient Perspective Andmentioning
confidence: 91%
“…Furthermore, immunotherapies have the potential to induce not only sustained, long-term benefits, but also lingering adverse effects. With these features in consideration, three articles in this CCR Focus examine conventional elements of clinical trials – endpoints, biomarkers and combination strategies – in the context of immunotherapy to highlight where standard principles prevail and where innovations are needed (13). The limitations and challenges encountered thus far in the design, implementation, and integration of immunotherapy clinical trials are discussed in the final article of this series (4).…”
Section: Introductionmentioning
confidence: 99%
“…hazard ratios of 0.5–0.6). In this CCR Focus , Anagnostou et al (1). examine the challenges of utilizing the traditional endpoints of ORR, PFS and OS in immuno-oncology clinical trials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As discussed by Anagnostou and colleagues in this series, the determination of clinically meaningful efficacy endpoints in immunotherapy trials is contentious, owing to atypical immune response patterns (101103). Delayed anti-tumor effect can lead to late separation of survival curves in randomized trials, affecting study duration and statistical power in detecting differences in the overall treatment effect (104).…”
Section: Goals and Challenges Of Immunotherapy Combinationsmentioning
confidence: 99%